Callus formation response from immature male flower explant of plantain banana (Musa acuminata x Musa balbisiana cv. Kepok) treated by 2,4-D and BAP - Dhiya Nabilla Ardhani; Maharijaya, Awang; Megayani Sri Rahayu (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Callus induction is an important step in indirect somatic embryogenesis. The aim of this study was to obtain an optimal medium for the callus formation of plantain bananas (cv. Kepok). The research was conducted from May to August 2022 at the Tissue Culture Laboratory of PT. ITCI Kartika Utama, Penajam Paser Utara District, East Kalimantan. The explant used an immature male flower of plantain banana (cv. Kepok). The experiment used a completely randomized design with two factors concentration of 2,4-D (1,2 and 4 ppm) and BAP (5, 10, and 15 ppm). The appearance of callus was monitored daily until it developed explants. On the final observation day, the percentage of explants with callus, as well as the color and texture of the callus, were assessed. The research findings suggest that the optimal medium for inducing callus in male banana flower explants was MS medium supplemented with 2 ppm 2,4-D and 5 ppm BAP. This medium resulted in calluses that exhibited a yellowish-white color and a compact texture. Keywords: callus morphology; genetic improvement; plant growth regulator; tissue culture; triploid banana